Sellers and Buyers’ Speech Acts in Traditional Markets of Soppeng Regency - Haslinda Haslinda (Edumaspul: Jurnal Pendidikan, 2025)
Speech acts of sellers and buyers in traditional markets in Soppeng Regency. This study aims to describe and determine how speech acts are performed by sellers and buyers in traditional markets in Soppeng Regency. This study is descriptive qualitative in nature. Data collection techniques were carried out in three ways, namely recording, observing and noting. This study was conducted using qualitative research methods with triangulation as the data collection technique. The data relevant to this study included data reduction, data presentation, conclusion drawing, and verification. The findings of this study were that there were three forms of directive illocutionary acts and one form of commissive illocutionary act. Based on the analysed data, a description was obtained covering directive acts of questioning, directive acts of commanding, and directive acts of granting permission. Meanwhile, the commissive illocutionary acts in the traditional market of Soppeng Regency include the commissive act of offering and the commissive act of promising.